Sensor less control of PMSM fed from three phase four switch inverter based on back EMF observer and sliding mode controller with fast reaching law - R, Ashok kumar; K, Balaji (International Journal of Engineering and Technology, 2018)
Closed Loop control of PMSM drives require rotor position and angular velocity information, the use of position sensor increases cost of the drive and increases complexity in motor construction. A position sensor less vector control technique is proposed where a back EMF observer is used to estimate motors speed and position signal. Back EMF observer method is simple and has high accuracy in estimating speed of PMSM motor. Permanent magnet synchronous motor is fed from a three-phase four-switch inverter and sliding mode controller is used as a speed regulator. Fast reaching law is added to sliding mode speed controller, which replaces constant switching gain function by variable switching function based on sliding surface. Variable switching function for SMC eliminates the chattering problem that occurs due to high value of constant switching gain. The proposed reaching law for sliding mode controller reduces the time taken for the controller to reach convergence and also increases robustness of the drive during parameter variation and full load conditions. Use of sensor less control technique and four-switch inverter reduced the overall cost of the drive whilst maintaining the performance of the system. Merits of pro-posed sensor less control technique and sliding mode controller with fast reaching law is verified by simulations using MATLAB/Simulink software.